Gambaran Kepribadian Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen Angkatan 2016 Berdasarkan Keberhasilan Akademik - Ervina Julien Sitanggang (Nommensen Journal of Medicine, 2019)
Academic success of medical students is influenced by cognitive and non-cognitive factors. Included in non-cognitive factors associated with academic success in the pre-clinical phase is the basic personality. The aim of this study was to describe the personality of Faculty of Medicine Universitas HKBP Nommensen students batch 2016 based on academic success. This research is a descriptive research. The subjects of this study were 50 students of the Faculty of Medicine Universitas HKBP Nommensen class of 2016 who were selected by the total sampling method. Personality data was obtained from the Indonesian Mental Health Test report which was undertaken by students while participating in the selection of the Faculty of Medicine Universitas HKBP Nommensen in the 2016/2017 academic year. Based on academic success in the first and second years, both students who were successful and those who did not succeed academically, the majority were in the big category for conscientiousness, while moderate for openness, extraversion, agreeableness and neuroticism domain. When compared based on academic success, in the first and second years a similar picture of personality was found in the group of students who succeeded and did not succeed academically.